2016
DOI: 10.1001/jamapsychiatry.2016.1161
|View full text |Cite
|
Sign up to set email alerts
|

Association of Marijuana Use With Blunted Nucleus Accumbens Response to Reward Anticipation

Abstract: Importance Marijuana use may alter ventral striatal response to reward, which may heighten susceptibility to substance use disorder (SUD). Cross-sectional studies have reported either increased ventral striatal response to reward or no difference in marijuana users compared with controls. Longitudinal research is needed to resolve the inconsistencies and disentangle preexisting susceptibility from the effects of marijuana use on neural function involved in reward responding. Objective To determine whether ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 47 publications
9
78
0
Order By: Relevance
“…Given that anhedonia is a manifestation of deficient reward activity [11] this finding is discordant with preclinical evidence of THC-induced dampening of brain reward activity and prior adult observational data showing that heavy or problematic marijuana use is associated with subsequent anhedonia [6] and diminished brain reward region activity during reward anticipation [27]. Perhaps the typical level and chronicity of exposure to marijuana use in this general sample of high school students was insufficient for detecting cannabinoid-induced manifestations of reward deficiency.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Given that anhedonia is a manifestation of deficient reward activity [11] this finding is discordant with preclinical evidence of THC-induced dampening of brain reward activity and prior adult observational data showing that heavy or problematic marijuana use is associated with subsequent anhedonia [6] and diminished brain reward region activity during reward anticipation [27]. Perhaps the typical level and chronicity of exposure to marijuana use in this general sample of high school students was insufficient for detecting cannabinoid-induced manifestations of reward deficiency.…”
Section: Discussionmentioning
confidence: 64%
“…Alternatively, repeated tetrahydrocannabinol (THC) exposure during adolescence produces enduring deficits in brain reward system function and anhedonia-like behavior in rodent models [26]. In observational studies of adults, heavy or problematic marijuana use is associated with subsequent anhedonia [6] and diminished brain reward region activity during reward anticipation [27]. Consequently, it is plausible that anhedonia may both increase risk of marijuana use and result from marijuana use.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear whether these changes are the cause or the consequence of cannabis use. While Martz and colleagues 8 did not find that past use correlated with nucleus accumbens activation at time 1, age at onset of use showed a trend-level association, which propagates the widely accepted idea that early-onset cannabis use is associated with brain alterations. Thus, because some of the individuals from the study were already using cannabis at time 1, there was no baseline (ie, precannabis use) comparison where one's cannabis-naive brain response could be compared with their own cannabis-exposed brain response to determine the true effect.…”
mentioning
confidence: 83%
“…This suggests the existence of predisposing factors, both genetic and environmental, that likely contribute to or interact with cannabis use. Indeed, Martz and colleagues 8 interpreted the inverse association between age at onset and time 1 nucleus accumbens response to a predisposing hypersensitivity of the reward system in the participants. In other words, these underlying factors not only increase the likelihood of cannabis use, but also increase the brain's susceptibility to the observed alterations.…”
mentioning
confidence: 99%
“…Finally, although most studies have reported that reward anticipation is altered in cannabis users relative to non-users [9][10][11], Lichenstein et al did not find a significant difference between the trajectory groups during the anticipatory period for reward. Rather, they found that the effects of escalation of use were observable only during the receipt of reward.…”
mentioning
confidence: 86%